2022
DOI: 10.3390/ijms23126836
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nano-miRNAs in Diagnostics and Therapeutics

Abstract: MicroRNAs (miRNA) are key regulators of gene expression, controlling different biological processes such as cellular development, differentiation, proliferation, metabolism, and apoptosis. The relationships between miRNA expression and the onset and progression of different diseases, such as tumours, cardiovascular and rheumatic diseases, and neurological disorders, are well known. A nanotechnology-based approach could match miRNA delivery and detection to move beyond the proof-of-concept stage. Different kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Nanofibre membranes are characterized by an exceptionally high surface-to-volume ratio with an extremely high number of pores. These properties favour nanofibre membranes for broad medical applications and for the production of medical devices, as recently demonstrated, e.g., for wound dressing, drug delivery, and biological sensing (Kenry and Lim 2017;Haider et al 2018;Bocková et al 2022;Coradduzza et al 2022;. The high density of the tiny pores and the ability to adjust their diameter also favour nanofibres for their application as highly effective liquid filters (Qin and Wang 2006;Sahto 2021;Zhou et al 2022).…”
mentioning
confidence: 87%
“…Nanofibre membranes are characterized by an exceptionally high surface-to-volume ratio with an extremely high number of pores. These properties favour nanofibre membranes for broad medical applications and for the production of medical devices, as recently demonstrated, e.g., for wound dressing, drug delivery, and biological sensing (Kenry and Lim 2017;Haider et al 2018;Bocková et al 2022;Coradduzza et al 2022;. The high density of the tiny pores and the ability to adjust their diameter also favour nanofibres for their application as highly effective liquid filters (Qin and Wang 2006;Sahto 2021;Zhou et al 2022).…”
mentioning
confidence: 87%
“…Furthermore, a heteroplasmonic nanostructure designed by the sequence-based specific identification of miR-107 targets induces the self-assembly of AuNPs and nanocuboids, resulting in an inherent peroxidase-like catalytic activity of AuNPs. 120 This technique can effectively identify the miR-107 gene present in prostate cancer patients by the application of surface-enhanced Raman scattering (SERS). 121 Researchers have also gained an immense interest in the field of H 2 O 2 -based biosensing, as it has emerged as an excellent ROS that is formed as a result of oxygen reduction.…”
Section: ■ Nanozymes As Biosensorsmentioning
confidence: 99%
“…FA-GO-AuNCs displayed peroxidase activity in a wide pH range, thus overcoming the peroxidase-like activity of free AuNCs under restricted pH conditions. Furthermore, a heteroplasmonic nanostructure designed by the sequence-based specific identification of miR-107 targets induces the self-assembly of AuNPs and nanocuboids, resulting in an inherent peroxidase-like catalytic activity of AuNPs . This technique can effectively identify the miR-107 gene present in prostate cancer patients by the application of surface-enhanced Raman scattering (SERS) .…”
Section: Nanozymes As Biosensorsmentioning
confidence: 99%
“…In recent years, with the continuous exploration of molecular biology, targeted therapies targeting specific genes and cells have been developed. Among them, the delivery of siRNA to tumor cells through nanomaterials has become a promising approach for cancer therapy 137 . Du et al demonstrated that delivery of circMDK siRNA via poly (β-amino esters) (PAEs) to a liver cancer model could effectively inhibit tumor progression.…”
Section: Potential Clinical Value Of Ncrnas Involved In Methylation M...mentioning
confidence: 99%